Articles of faith and organized religion in Islam: historicity and faith and its implications - Kazmi, Yedullah (Islamic Research Institute, 2008)
In order to act resolutely and effectively in history Muslims need to develop critical historical consciousness that would furnish them with the intellectual tools to understand history in light of their faith and help them act out their faith in light of history. This is one message of the Sunnah of the Prophet (peace be upon him) that is often over looked. In order to understand why critical historical consciousness has failed to develop among Muslims we need to cast on the history of Muslims and particularly of Muslim education a critical eye. This may shed some light on why Muslims who once shaped history are now cowed and rendered helplessly by historical necessities.